2011
DOI: 10.1074/jbc.m110.204420
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Complex between α-Naphthoflavone and Human Cytochrome P450 1B1

Abstract: The atomic structure of human P450 1B1 was determined by x-ray crystallography to 2.7 Å resolution with ␣-naphthoflavone (ANF) bound in the active site cavity. Although the amino acid sequences of human P450s 1B1 and 1A2 have diverged significantly, both enzymes exhibit narrow active site cavities, which underlie similarities in their substrate profiles. Helix I residues adopt a relatively flat conformation in both enzymes, and a characteristic distortion of helix F places Phe 231 in 1B1 and Phe 226 in 1A2 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 30 publications
(27 reference statements)
2
155
0
Order By: Relevance
“…Of these six P450s, 1A2 exhibits the smallest and narrowest active site (Sansen et al, 2007). This architecture is conserved in structures of P450s 1A1 (Walsh et al, 2013) and 1B1 (Wang et al, 2011), and the narrow hydrophobic cavity is consistent with the roles of these enzymes in metabolism of polycyclic aromatic hydrocarbons. This narrow cavity is reinforced by the passage of helix F below helix G, and this redirection of the F helix is associated with a distortion of the F helix as it passes over the active site cavity (Fig.…”
Section: Introductionmentioning
confidence: 65%
“…Of these six P450s, 1A2 exhibits the smallest and narrowest active site (Sansen et al, 2007). This architecture is conserved in structures of P450s 1A1 (Walsh et al, 2013) and 1B1 (Wang et al, 2011), and the narrow hydrophobic cavity is consistent with the roles of these enzymes in metabolism of polycyclic aromatic hydrocarbons. This narrow cavity is reinforced by the passage of helix F below helix G, and this redirection of the F helix is associated with a distortion of the F helix as it passes over the active site cavity (Fig.…”
Section: Introductionmentioning
confidence: 65%
“…To make this follow-up experimental functional characterization more efficient, we first utilized a computational modeling and docking strategy to estimate the substrate range and catalytic potential of CYP63A2. Comparison of the CYP63A2 3D model with the crystal structures of P450s from prokaryotes (42,43) and higher eukaryotes (44)(45)(46) indicated that CYP63A2 is the largest among the analyzed P450s (Fig. 2 and Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This change in the amino acids sequences of the protein may alter its expression, or the catalytic activity, which may induce diseases as a phenotype [6]. The crystal structure of the CYP1B1 was determined [7], it has a narrow slot-like active site that is similar to that of CYP1A1; however, the residues around the edge of the active sites are different for specific binding of substrates and inhibitors [7]. Using the reverse transcriptase-coupled polymerase chain reaction (RT-PCR), CYP1B1 mRNA was detected in hepatocytes, lymphocytes, and uterus [8].…”
Section: Introductionmentioning
confidence: 99%